INSTITUTIONAL MECHANISMS AND MANAGEMENT TOOLS TO ADMINISTER AGGLOMERATIONS IN BRAZIL - P. V. Stroev; M. I. Kan (Финансы: теория и практика, 2017)
The article highlights the basic principles of operation of management tools used today to administer the agglomerations in Brazil.The article considers the system to manage urban agglomerations in the state of Sao Paulo in view to use the positive experience while creating similar management systems to administer agglomerations in the Russian Federation. In addition, it shows the role of the state, regional and municipal authorities in the creation of metropolitan areas (agglomerations), and identifies the mechanisms for funding and inter-municipal cooperation between agglomerations. The institutional management system and implementation of planning functions by the public authorities in the Brazilian state of Sao Paulo is of great interest in terms of application of best practice in the Russian conditions. A fundamentally important aspect of the experience of Brazil is the relations between the state and regional authorities and agglomerations. A rather valuable experience for Russia is the availability in the state of Sao Paulo of special governing bodies at both the level of agglomerations and the level of macro-region incorporating several agglomerations. The Brazilian experience can be used in Russia since its management bodies which are being created now will carry out planning, management, coordination, monitoring and control functions in the agglomeration integrating several municipalities.